Коррекция погрешностей в высокоточных импульсных лазерных дальномерах - Брагинец, И.А.; Зайцев, Е.А.; Кононенко, А.Г.; Масюренко, Ю.А.; Ниженский, А.Д.; Латенко, В.И.; Орнатский, И.А. (Технічна електродинаміка, 2012)
The application of the proposed algorithms and the functioning of the circuit solutions for the correction of errors in pulsed laser range finders, is presented and described in the corresponding block diagram of the range finder. Particular attention is paid to the characterization of exposure correction used to correct the error that occurs when the amplitude and shape of the object under control of the reflected light signal. It is shown that application of the method of least squares, based on the evaluation of the results of experimental studies, can significantly reduce the uncertainty due to linearity is not converting units of pulse ranging systems. The tables containing the numerical values of the parameters of the correcting influence, and a table of errors of distance measurement, computed on the basis of the results of experimental studies performed on the model of the pulsed laser.